What Is and How to Improve the Local History Material in History Learning - Winarti, Murdiyah (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The simple formula used to explain the local history in this paper is the history that tells about the dynamis life of a community with its culture in an area, a certain regionality. In the â€œlocalityâ€ perspective of location or geography aspect which include the village, city, region, and province and its variety, Indonesia would have many of it. However, the local history has a strategic role while providing a wide possibility in improving the national history writing. In term of theme, the posibility for the local hidtory materials writing and develoment is interesting and open. However, there is a challenge, which is the limitation in gaining the historical resources, particularly the written one. Therefore, the local history material development in Indonesia relies on the oral tradition and oral history.